Ensino intradisciplinar de Matemática através da resolução de problemas: o caso do Algeblocks - Silva, Lilian Esquinelato da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Esta pesquisa tem como objetivo investigar como o material manipulativo Algeblocks e a Metodologia de Ensino–Aprendizagem–Avaliação de Matemática através da Resolução de Problemas contribuem para o Ensino Intradisciplinar. Esta pesquisa foi desenvolvida seguindo a Metodologia Científica de Romberg–Onuchic, apresentada por Onuchic e Noguti (2014). A fundamentação teórica desta pesquisa tem como base três variáveis-chave: Conexões no Ensino de Matemática, Materiais Manipulativos e Resolução de Problemas. Procuramos investigar pesquisas que trabalham o ensino de Matemática fazendo conexões entre diferentes ramos da Matemática e as contribuições do Algeblocks para o desenvolvimento do projeto pedagógico de Matemática, ao adotar a Metodologia de Ensino–Aprendizagem–Avaliação de Matemática através da Resolução de Problemas. Para tanto, estabelecemos como procedimentos da pesquisa a elaboração de um Projeto Pedagógico e sua aplicação em uma turma de 8º ano do Ensino Fundamental de uma escola estadual da rede pública de ensino da cidade de Rio Claro - SP. Esse Projeto envolve o Ensino–Aprendizagem–Avaliação de Matemática com uso dos Algeblocks trabalhando a compreensão de conceitos matemáticos. Percebemos que o trabalho do professor de Matemática ao fazer uso da Metodologia de Ensino–Aprendizagem–Avaliação de Matemática através da Resolução de Problemas dá a possibilidade, com o uso do Algeblocks, de trabalhar conceitos matemáticos realizando as conexões entre diferentes ramos da Matemática.

This research aims to investigate how the Algeblocks manipulative and Methodology of Mathematics Teaching-Learning-Evaluation through Problem Solving contribute to Intradisciplinary Teaching. This research was developed following the Scientific Methodology of Romberg–Onuchic presented by Onuchic and Noguti (2014). The theoretical basis of this research is based on three key variables: Connections in Teaching Mathematics, Manipulative Materials and Problem Solving. We seek to investigate researches that work the teaching of Mathematics making connections between different branches of Mathematics and the contributions of the Manipulative Material for the development of learning of Mathematics by adopting the Methodology of Mathematics Teaching-Learning-Evaluation through Problem Solving. Therefore, we established as research procedures the elaboration of a Project and its application in an 8th grade class of Elementary School of a state school of the public school of the city of Rio Claro - SP. This Project involves the teaching-learning-evaluation of Mathematics with use of the Algeblocks making the concrete representations of abstract concepts. We realized that the work of the Mathematics teacher in making use of the Methodology of Teaching-Learning-Evaluation of Mathematics through Problem Solving gives the possibility, with the use of Algeblocks, of working mathematical concepts making the connections between the different branches of Mathematics.
Intradisciplinary teaching of Mathematics through problem solving: the case of the Algeblocks
Keywords: Resolução de problemas; Algeblocks; Ensino-aprendizagem-avaliação; Ensino intradisciplinar; Aritmética; Álgebra; Geometria; Problem solving; Teaching-learning-evaluation; Intradisciplinary teaching; Arithmetic; Algebra; Geometry